Combined Plyometric Trainings and its Effectiveness in Improving Muscle Strength and Power among Male Adolescents - Putera, Shidqi Hamdi Pratama; Widodo, Achmad; Wahyudi, Heri; Wismanadi, Himawan; Tuasikal, Abdul Rachman Syam; Sholikhah, Anindya Maratus (Physical Education Theory and Methodology, 2025)
Objectives. This study aimed to evaluate the impact of combined plyometric training on increasing muscle strength and explosive power among male high school students. Materials and methods. The study was performed using quasi-experimental design with randomized pretest and posttest design. Fourty-five students were divided into three groups: SKSQ (squat jump and skater hops); IODJ (ins and outs jump and depth jump); CTRL (conventional training program). The treatments were given three times a week for six weeks. The strength and power of muscle legs were assessed before and after the intervention using Leg Dynamometer and Jump MD. The statistical analysis was conducted using SPSS 29 and GraphdPad Prism. Results. A paired sample t-test revealed that each group experienced a significant increase (p<0.05), with the most notable improvements in strength (Δ=5.40%) and power recorded in SKSQ (Δ=18.33%). In contrast, CTRL showed the smallest yet significant gains in both strength and power. From this findings, participants in SKSQ and IODJ demonstrated a greater increase compared to those in the control group. Conclusions. The results highlighted the effectiveness of combined plyometric trainings in enhancing athletic performance. Further research could explore the underlying mechanisms of these adaptations.